2017
DOI: 10.1002/asna.201713403
|View full text |Cite
|
Sign up to set email alerts
|

The variability of magnetic activity in solar‐type stars

Abstract: This article reviews the current knowledge and status of investigations on the variable magnetic activity of cool stars. We discuss the Sun in the context of solar-type stars, highlighting peculiarities and common features in terms of its magnetic activity and variability over different time scales. We examine how both theory and observations are providing new clues about the main physical processes that generate magnetic fields in the interior of cool stars, as well as about those that lead to evolving stella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 219 publications
(258 reference statements)
1
19
0
Order By: Relevance
“…The first asteroseismic evidence of variations in stellar activity were found in an F5 V star observed by CoRoT [7,8], HD 49933. For this star García et al [9] found that not only did the frequencies vary Stellar magnetic activity also manifests in variability of stellar luminosity [see, e.g., 31, and references therein]. Over the solar cycle the total irradiance is found to change by about 0.1% in temporal correlation with solar activity [32].…”
Section: Introductionmentioning
confidence: 91%
“…The first asteroseismic evidence of variations in stellar activity were found in an F5 V star observed by CoRoT [7,8], HD 49933. For this star García et al [9] found that not only did the frequencies vary Stellar magnetic activity also manifests in variability of stellar luminosity [see, e.g., 31, and references therein]. Over the solar cycle the total irradiance is found to change by about 0.1% in temporal correlation with solar activity [32].…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, strictly speaking, the value of B s is obtained from the average value of the radial magnetic field B c at the corona boundary r = R c , recalculated by considering the conservation of the magnetic flux by the star radius, B s R 2 s = B c R 2 c . On the other hand, it is known that the magnetic fields of solar-type stars can lie in the range from about 0.1 to several Gauss [63,64]. In addition, the host stars for hot Jupiters can be not only of the solar type, since their spectral classes lie in the wide range from class F to class M. In addition to the radial component, the azimuthal component of the magnetic field is also present in the stellar wind, which is due to the star proper rotation.…”
Section: Calculation Examplementioning
confidence: 99%
“…These variations are an important forcing term for the evolution of the climate on Earth (e.g., Lean 2017). In recent years, solar irradiance variability studies have also been motivated by the necessity for achieving an understanding of and modeling stellar variability (Fabbian et al 2017;Faurobert 2019) which, in turn, may hamper exoplanet detectability (e.g., Cegla 2019) and affect both the determination of the physical properties of exoplanet atmospheres (e.g., Kowalski et al 2019) and the abundance of biomarkers (e.g., Grenfell 2017).…”
Section: Introductionmentioning
confidence: 99%